Potential of Hanjeli (Coix lacryma-jobi) as an antifungal Microsporum Gypseum Causes Skin Infections: Extract, Boiled Water, Kombucha, and Bath Soap - Tri Saptari Haryani; Mutiara Siti Nurfajriah; Cecep Sudrajat; Firman Rezaldi; Tri Yudianto; Rifkarosita Putri Ginaris; Sukardi Sugeng Rahmad (Postgraduate, University of Mataram, 2025)
Job's tears (Coix lacryma-Jobi L.) are known to contain chemical compounds of the alkaloid, flavonoid and tannin groups that have the potential as antifungals. Microsporum gypseum is one of the dermatophyte fungi that causes dermatitis, a disease that infects skin of both animals and humans. The study aims to test the activity and determine optimal concentration of Job's tears seed extract, Job's tears seed boiled water, Job's tears leaf kombucha, and Job's tears seed extract bath soap formulation as antifungals against Microsporum gypseum which causes skin disease infections. The research method used agar diffusion with the well technique (Agar Well Diffusion), the research parameters included phytochemical tests of the extract, measuring diameter inhibition area. The results phytochemical test obtained alkaloid compounds, and results of activity test of the Job's tears seed extract formulation, Job's tears seed boiled water, Job's tears leaf kombucha, and Job's tears seed extract bath soap obtained optimal diameter of the inhibition area overall at an extract concentration of 40%. Conclusion, activity of ethanol extract of hanjeli seeds, boiled water of hanjeli seeds, hanjeli leaf kombucha, and hanjeli seed extract bath soap at a concentration of 40% have antifungal activity against Microsporum gypseum which causes skin diseases.